Cybersecurity awareness mobile app for secondary school students: LetSecure - Jafri, Azma Melia; Jamaluddin, Nur’ Ain Zulaikha; Zulkifli, Zahidah (2021)
The increasing number of cybersecurity cases recently is not something new. Moreover, during this pandemic and lockdown, the demand for internet services is extremely high, which has changed people's lifestyles. People spend more time using the internet and devices but at the same time, many of us still lack cybersecurity awareness especially people who do not have formal knowledge on IT and cybersecurity. Hence, this project, LetSecure Application, aims to create awareness of cybersecurity among secondary school students and to assist them in choosing the best course in higher education and developing their career plan in the area of ICT and cybersecurity. This application could be utilized in teaching cybersecurity to them through the quiz module without changing the existing school curriculum for an optimum learning experience. In addition, this application offers guidance and tips on how users can prevent themselves from being cybersecurity victims. Another aim is to provide information about cybersecurity and give exposure to users on choosing cybersecurity as a career. LetSecure Application has been developed by Flutter as a framework and using Dart programming language. Firebase for the authentication while Firestore to store the database of the users. The User Acceptance has been conducted with the positive results from the two of the target users which are the counselors and the student. The suggestion such as to put the bilingual in the application to make it easy for the students. For the future plan, this application can be implemented to other schools in Malaysia. This application also inlines with the sustainable development goals which are; Quality education and Sustainable Cities and Communities.